2020
DOI: 10.1289/ehp6301
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Morphometric and Statistical Approach to Assess Nonmonotonicity in the Developing Mammary Gland of Rats in the CLARITY-BPA Study

Abstract: BACKGROUND: The Consortium Linking Academic and Regulatory Insights on Bisphenol-A (CLARITY-BPA) is a rare collaboration of guidelinecompliant (core) studies and academic hypothesis-based studies to assess the effects of bisphenol A (BPA). OBJECTIVES: We aimed to a) determine whether BPA showed effects on the developing rat mammary gland using new quantitative and established semiquantitative methods in two laboratories, b) develop a software tool for automatic evaluation of quantifiable aspects of the mammary… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(60 citation statements)
references
References 74 publications
3
57
0
Order By: Relevance
“…For some organs such as the mammary gland, there was a break between 25 and 250 μg/kg/day doses in all datasets at all ages, which was analyzed by specific statistical methods appropriate for non-monotonicity. The fact that this break is present in all time points analyzed and in the vast majority of the specific measurements clearly indicate that the NMDRC is not spurious [ 17 ]: on the contrary, it shows that there is an underlying causal relationship.…”
Section: Integrated Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For some organs such as the mammary gland, there was a break between 25 and 250 μg/kg/day doses in all datasets at all ages, which was analyzed by specific statistical methods appropriate for non-monotonicity. The fact that this break is present in all time points analyzed and in the vast majority of the specific measurements clearly indicate that the NMDRC is not spurious [ 17 ]: on the contrary, it shows that there is an underlying causal relationship.…”
Section: Integrated Discussionmentioning
confidence: 99%
“…Results of the Core guideline study were published in a single report [ 2 ], and results of several academic studies were published independently in peer-reviewed journals [ [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] ]. Assessments of the overall study design [ 18 , 19 ] and a summary of available datasets from multiple CLARITY-BPA studies [ 20 ] are also published in peer-reviewed journals.…”
Section: Introductionmentioning
confidence: 99%
“…However, for each outcome there is a lack of consistency across existing studies." For the CLARIY-BPA study by Montevil (Montevil et al 2020) recently highlighted (Soto et al 2021) as a key effect observed in CLARITY and discussed here in Appendix A, EFSA concluded "In the absence of any clear biological explanation why the dose response curve may behave in such non-linear manner and taking into consideration lack of overall significance (from the NULL model) the pattern observed may be a result of overfitting of the data rather than a true biological relationship. In any case, the findings from this paper need to be replicated before any conclusions on relevance and adversity can be made.…”
Section: Nmdr Effects For Bpa?-the View Of Efsamentioning
confidence: 98%
“…Although the CLARITY-BPA study was conducted blinded, some of these assessments are post hoc analyses after un-blinding. See Appendix A for a detailed discussion on the study on the mammary gland development (Montevil et al 2020) highlighted as the study providing "the strongest evidence of non-monotonicity within the CLARITY study" by Soto et al (Soto et al 2021).…”
Section: Science's First Principle: Replicationare Low-dose Nmdr Effects Replicated In Independent Repetitions?mentioning
confidence: 99%
“…Finally, a few other reports from the CLARITY project have suggested some indications of NMDR. The outcomes assessed, including different measures of fetal urogenital sinus (Uchtmann et al., 2020 ), mammary gland response (Montévil et al., 2020 ), modest changes in % basophil and serum bile acid concentrations (Badding et al., 2019 ). A detailed assessment of these studies is provided in Annex A .…”
Section: Assessmentmentioning
confidence: 99%